Emergency blood transfusion service (report) (1939)
1939 1939 1930s 5 pages - 3 - Were they to do so there would be a marked tendency to dehydrate food stuffs to a considerable degree. Of recent years forced air cooling units, sometimes termed "blowers", employing fans of many times the capacity, have been used in dairy rooms where humidity control is of no importance. Such rooms are the only ones which would be quite suitable for blood storage. All other types will have disadvantages (3) and (4), above, but not to the same degree as domestic type units. Blood Storage Refrigerators It is possible to obtain to-day, refrigerators thoroughly and absolutely suitable for blood storage, and with none of the above disabilities. The main requirements for a unit for hospital use can be stated as under:- (a) There should be no possibility of freezing any blood wherever it may be stored in the refrigerator. (b) It should be unnecessary to switch off the refrigerator for defrosting so that a constant temperature can be maintained continuously. (c) The temperature should be the same at all parts of the refrigerator. (d) Forced air circulation should be employed to ensure condition (c) above, and to give more rapid removal of heat from the contents. (e) The machine should be fully automatic to minimize temperature variations, and secondary safety controls should be fitted. It is unnecessary to emphasize that units should be obtained only from a thoroughly reliable manufacturer, and one who is able to give immediate and efficient night and day after-sales service should it be required. Investigation of the products offered by Frigidaire Limited indicates that this firm has already manufactured at its Hendon works a number of different types of blood storage cabinets for H.M. Government, and that they have available two sizes particularly suitable for hospital use with capacities of 100 and 33 pint bottles respectively. These cabinets can be purchased in quantities at prices of approximately £95. 0s. 0d. and £50. 0s. 0d. respectively whilst larger cold stores can be supplied to order. 292/845.2/4/51